2019
DOI: 10.1016/j.ejvs.2018.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Iliofemoral Stenting for Post-thrombotic Syndrome

Abstract: WHAT THIS PAPER ADDS Endovascular stenting is relevant to the management of post-thrombotic syndrome with chronic obstruction in iliofemoral venous segment. Although this systematic review demonstrates that the quality of evidence for iliofemoral stents is weak, venous stenting has the potential to be effective, with extremely rare occurrences of peri-operative complications. This review may assist in clinical decision making and guide future research. Objective: Stent placements are considered as a treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 45 publications
3
26
0
Order By: Relevance
“…In fact, a reappraisal of invasive treatments in PTS has been recently highlighted [89]. In view of the contrasting evidence for venoplasty ± stenting in PTS patients [90][91][92], this procedure is being reserved to selected cases where other treatments have failed and the main risk factors (e.g., obesity, pump dysfunction, thrombophilia) have been already addressed, with little benefit.…”
Section: Deep Vein Thrombosis and Post-thrombotic Syndromementioning
confidence: 99%
“…In fact, a reappraisal of invasive treatments in PTS has been recently highlighted [89]. In view of the contrasting evidence for venoplasty ± stenting in PTS patients [90][91][92], this procedure is being reserved to selected cases where other treatments have failed and the main risk factors (e.g., obesity, pump dysfunction, thrombophilia) have been already addressed, with little benefit.…”
Section: Deep Vein Thrombosis and Post-thrombotic Syndromementioning
confidence: 99%
“…42 While there are innumerable studies reporting excellent patency rates and clinical outcomes following deep vein stenting for IFVO, the quality of evidence is low. [43][44][45] Most available studies are small, retrospective, single-site evaluations. 46 A systematic review conducted by Seager et al identified no randomised controlled trials, cohort studies or case-control studies.…”
Section: Discussionmentioning
confidence: 99%
“…A GRADE assessment 47 demonstrated the quality of the evidence to be "low" for ulcer healing and "very low" for other outcomes. 44 Despite the weak quality of evidence, deep vein stenting is relatively effective and safe with low incidence of peri-operative complications and high patency rates, 9,[43][44][45][46] and should be considered as a treatment option while the evidence base improves. 44 Post-operative anticoagulation decreases complication rates such as in-stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analyses have demonstrated the majority of operators have followed the Neglan and Raju technique (5) by landing their stents a variable distance into the IVC (1,21). Reasons for this include difficulty identifying the confluence, ensuring lesion crossing, and overcoming shortcomings in available stent technology (4).…”
Section: Discussionmentioning
confidence: 99%